بلاغة النص الديني في خطب الإمام الحسين (عليه السلام): حقوق الإنسان أنموذجاً - الحلو, وسن منصور (Al-Adab Journal, 2019)
It is noted that the issue of tyranny and the right to resist it is an eternal issue, and it is noted that the resistance of tyranny and tyranny was clearly defined by Imam Hussein (peace be upon him), a picture and reflection of the bitter reality experienced by Imam (peace be upon him) and his family and his companions, was the disruption of security and order and the spread of corruption in his society Peace be upon him) and the suffering of people from difficult political, economic and military conditions, which encouraged the imam to carry out this legitimate resistance against the individual ruler represented by Muawiya and his son Yazid. His speeches came, especially in the days leading up to the known battle.Resistance is a legitimate right for all, whether this resistance comes from an individual or a group against governments, leaders and rulers who rule with an iron fist. His speeches have come to him with a number of rhetoric that we can monitor.